A link–adapted fragment and rate matching (FaRM) MAC protocol for wireless LANs. (16th October 2014) - Shih, Kuei–Ping; Chou, Chien–Min; Li, Chun–Chih; Cheng, Li–Jie
The paper proposes a fragment and rate matching (FaRM) MAC protocol for wireless LANs to resist the frequent change of channel quality so as to increase network throughput. In wireless transmissions, channel quality varies with time. The FaRM protocol estimates channel quality by detecting current signal–to–noise ratio (SNR) through frame exchanges. A finite state Markov chain (FSMC) is utilised to predict the variation in the channel conditions during the next frame transmission. According to the results obtained from the FSMC, the FaRM protocol enables the sender to dynamically select an appropriate transmission rate as well as an acceptable fragment length to transmit, such that the reliability and time of this transmission can be improved. As a result, the FaRM protocol can not only obtain better network throughput through the selection of the high transmission rate, but it can also increase the successful transmission rate by the determination of a suitable fragment length. Simulation results show that the FaRM protocol has better performance, higher transmission reliability, and lower transmission delay by FaRM in comparison to the related work.